The use of the General Medical Services prescription database for pharmacoepidemiological studies in Ireland - Williams, David (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2003)
Pharmacoepidemiology may be divided into three main subdivisions, namely pharmacovigilence, drug utilisation and prescribing quality. An aim of this thesis was to demonstrate the usefulness of the General Medical Services (GMS) prescription database to perform pharmacoepidemiological studies in Ireland. This database provides information on some 30% of the population who receive approximately 70% of prescriptions. In the field of pharmacovigilence I demonstrated the effect of external forces particularly the media and regulatory advice on prescribing patterns within the GMS which led to a marked decline in the use of third generation contraceptive steroids and cotrimoxazole. An attitudinal survey on adverse drug reaction(ADR) reporting by doctors confirmed the findings of other workers regarding the reasons for not reporting ADRs and highlighted the need to improve reporting rates.
Keywords: Medicine, Ph.D.; Ph.D. Trinity College Dublin